Conservation Environmental Sustainability in The Perspective of Islamic Legal Philosophy - Munib, Munib; Patrajaya, Rafik; Ihsan, Reza Noor; Amin, Muhammad (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2022)
This paper is motivated by the existence of central issues regarding environmental damage that are increasingly concerning, both those reported through the mass media and those circulating on national and international television broadcasts. Therefore, it is necessary to have a solution for handling and to bridge environmental issues studied across various disciplines of knowledge, in this case, using an Islamic legal philosophy approach. This research method is a normative legal study using the perspective of Islamic legal philosophy. This study indicates that religion has tended to focus more on matters of ritual aspects without looking further at the meanings of the symbols of religious teachings themselves, particularly if they are associated with awareness to conserve the environment adequately because it involves the benefit of many people. This paper aims to reveal the sides of religious teachings, especially Islamic teachings that raise awareness of the environment. Because in Islamic doctrine, it is taught about how to behave by values or norms concerning human relations with the universe (hablu minal 'alam). The philosophical view of Islamic law is that humans are essentially entrusted with managing the planet and its contents as caliphs on earth, particularly in maintaining and managing the natural resources in a trustworthy manner to avoid mafsadah (damage) that threatens all human life. The findings of this study indicate that the Islamic legal philosophy provides a living guide for how to treat the environment in both peaceful and emergency situations. This can be accomplished by not destroying plants (trees), not throwing dirt anywhere, managing the land to be productive, removing obstacles in the flow of people's movement, and sharing responsibility for sustainably managing forests, water, and energy.